Natural death of the employees at workplace in Ukraine in the dynamics of 2015-2020 (Environment & Health, 2021)
Introduction: In recent years, there has been a gradual decline in occupational traumatism in Ukraine, but an in-depth analysis of the data shows that statistics does not fully reveal the complexity of the current situation on occupational traumatism and the quality of its registration and record-keeping, especially in case of sudden death at a workplace. According to the Resolution of the Cabinet of Ministers of April 17, 2019 № 337 on «Procedure for investigation and record-keeping of the incidents, occupational diseases, and accidents at the production» (with changes made in accordance with the Resolution of the Cabinet of Ministers № 1, 05.01.2021) the amendments were made where the circumstances of an accident and / or acute occupational disease (poisoning), cases of sudden death were recognized as related to production (according to the Article 52, paragraphs 6-8).Objective: We identified the regularities of the formation of the indicators of natural death at workplace of the employees over 2015-2020 in Ukraine.Materials and methods: According to the data of the State Statistics Committee of Ukraine and the State Labour Service of Ukraine, we performed the analysis of natural deaths of the employees at workplace in the dynamics of monitoring by the types of economic activity, occupations and causes over 2015-2020 and established the ways for the improvement of their record-keeping. Statistical data were evaluated with the help of rankings, methods of generally accepted statistical analysis.Results and discussion: From 2015 to 2019, the number of the accidents at production, registered and recognized as insured events, decreased from 4,260 to 3,876 (by 9.0%), and the number of the fatal traumatized increased from 375 to 422 (by 11.1%). In 2020, the number of the accidents (A) increased up to 6121 (by 30.4%), and the accidents with fatal consequences increased up to 653 (by 42.5%), mainly due to the diseases of circulatory system and COVID-19. In recent years, there has been an increase in sudden deaths (SD) and «rejuvenation» of the contingent of working people.The problem of natural death is actual worldwide and according to the WHO, makes up 5-7%. Among those who died of natural causes, young people aged 20-39 years make up a significant proportion, mainly due to circulatory diseases and COVID-19. It was established that in the dynamics of 2015-2020, there were 4861 cases of natural death (ND) at workplace in Ukraine, which are 8.0-16.2 per 100 thousand working population and 27.2-55.0 per 100 thousand population working under harmful working conditions against 5.3 and 14.1 in 2012. The analysis of cases of ND in terms of gender, age and length of service shows that more than 77.0% are men aged 20-60 years old. The distribution of cases of ND at the workplace in Ukraine by the branches of industry shows that the socio-cultural sphere (30.0-55.2%), transport (16%), engineering and metallurgy (10.5-6.6%), coal and mining industry (4.2-2.4%) are the main ones. The cases of ND at workplaces from diseases of the circulatory system in the employees of social sphere and transport, miners of coal mines have been analyzed in details. The methods of prevention of ND at workplace are proposed.Conclusions: 1. The problem of natural death at the workplace requires an additional legislation to determine the circumstances of death connected with the working conditions or the feautures of the production process.2. The most frequent cases of ND at the workplace in Ukraine are registered among employees of the socio-cultural sphere (30.0-55.2%), transport (16%), mechanical engineering and metallurgical industry (10.5-6.6%), construction and road construction, agro-industrial complex , coal and mining industry (4.2-2.4%).3. Diseases of the circulatory system (acute cardiovascular failure (heart attack, stroke), coronary heart disease, heart and lung failure on the background of nervous and emotional stress, lack of sleep, the presence of a complex work schedule (daily, 12 hours, night shifts, which requires a separate study of causation) and impact of the adverse factors of the working environment were the main causes of ND in the employees.4. Prevention of ND is in the field of the restoration of the system of providing medical care to employees, improvement of the quality of preventive medical examinations, pre-shift control, occupational selection.
Keywords: natural death at workplace; heart failure; branches of industry